Beginning reading in Hiligaynon - Solido, Caridad Castillano 1940- (s.n.], 1969)
The aim of the study is to present a method of teaching beginning reading in Hiligaynon, the official dialect of the provinces comprising Western Visayas. This is adapted from the method developed by Nooraihan and Urbano in their book "Bumasa Tayo at Sumulat." This proposed approach to beginning reading in Hiligaynon is considered in order to help minimize, if not eliminate, non-readers in Hiligaynon. It aims to aid teachers who desire to have a wider understanding of the principles and teaching techniques of the phono-syllabic method, which combines the resources of the eye and the ear in units of sights and sounds, as basic elements in learning. It further aims to make the learning of reading easy through a systematic presentation of sounds sequentially arranged and to develop in children a tool for individual word attack.